2002
DOI: 10.1002/cncr.101970.abs
|View full text |Cite
|
Sign up to set email alerts
|

The American Cancer Society Cancer Prevention Study II Nutrition Cohort

Abstract: This new cohort of both men and women promises to be particularly valuable for the study of cancer occurrence, mortality, and survival as they relate to obesity and weight change, physical activity at various points in life, vitamin supplement use, exogenous hormone use, other medications (such as aspirin and nonsteroidal anti- inflammatory drugs) and cancer screening modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
207
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 144 publications
(211 citation statements)
references
References 0 publications
2
207
0
2
Order By: Relevance
“…Briefly, the consortium pools genotyping information and extensive questionnaire data from large, well established prospective cohorts based in the USA and Europe. Cases of invasive primary breast cancer and matched controls were identified from five participating American cohorts: the American Cancer Society Cancer Prevention Study-II,21 the Harvard Nurses’ Health Study (NHS),22 the Hawaii-Los Angeles Multiethnic Cohort,23 the Prostate, Lung, Colorectal and Ovarian Cancer Screening Trial24 and the European Prospective Investigation into Cancer and Nutrition (EPIC) 25. Depending on the study cohort, cancer cases were identified by linkage with population-based tumour registries and/or self-reported and confirmed through medical records.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, the consortium pools genotyping information and extensive questionnaire data from large, well established prospective cohorts based in the USA and Europe. Cases of invasive primary breast cancer and matched controls were identified from five participating American cohorts: the American Cancer Society Cancer Prevention Study-II,21 the Harvard Nurses’ Health Study (NHS),22 the Hawaii-Los Angeles Multiethnic Cohort,23 the Prostate, Lung, Colorectal and Ovarian Cancer Screening Trial24 and the European Prospective Investigation into Cancer and Nutrition (EPIC) 25. Depending on the study cohort, cancer cases were identified by linkage with population-based tumour registries and/or self-reported and confirmed through medical records.…”
Section: Methodsmentioning
confidence: 99%
“…Women in this analysis were participants in the Cancer Prevention Study (CPS) II Nutrition Cohort, a prospective study of cancer incidence among men and women from 21 states in the US, established by the American Cancer Society in 1992 [20]. At enrollment, 86,404 men and 97,788 women completed a 10-page, self-administered questionnaire on medical, dietary, reproductive, and lifestyle variables.…”
Section: Methodsmentioning
confidence: 99%
“…Calcium, vitamin D, and dairy product intakes were measured in 1992 to 1993 [20] using a semi-quantitative 68-item food frequency questionnaire (FFQ), which is a modification of the brief 'Health Habits and History Questionnaire' developed by Block and colleagues [22]. Dietary and total nutrient intakes were estimated using the Diet Analysis System version 3.8a (Division of Cancer Prevention and Control, National Cancer Institute, Bethesda, MD, USA) [23].…”
Section: Methodsmentioning
confidence: 99%
“…This nested case–control study was designed within seven prospective cohort studies: the Cancer Prevention Study-II Nutrition Cohort (CPS-II),20 the Carotene and Retinol Efficacy Trial,21 the European Prospective Investigation into Cancer and Nutrition (EPIC),22 the Multiethnic Cohort Study (MEC),23 the Prostate, Lung, Colorectal, and Ovarian Cancer Screening Trial,24 the Prostate Cancer Prevention Trial (PCPT)25 and the Women’s Health Initiative (WHI) 26. All cohorts, apart from EPIC, were conducted within the US population.…”
Section: Methodsmentioning
confidence: 99%